The Assessment and Reduction of Carbon Oxides Emissions at Electric Arc Furnaces – Essential Factors for Sustainable Development. (2015) - Iluţiu-Varvara, Dana-Adriana; Mârza, Carmen Maria; Sas-Boca, Ioana-Monica; Ceclan, Vasile Adrian
Abstract: Carbon oxides (COx ) have a negative impact on the steelworkers, environment and populations. The aim of this paper is to assess the COx emissions from steelmaking in the electric arc furnaces, in order to improve the gaseous emissions management, an essential factor for sustainable development, by identifying the most polluting technological stages of this process. The experimental researches were carried out on two electric arc furnaces with alkaline lining. The measurement of COx emissions was performed using a Maxilyzer computer for burned gases automated analysis. After evaluating the emissions of COx during steelmaking in electric arc furnaces, it results that: the most significant emissions have been generated at the end of the melting and refining stage; in terms of pollution by COx, the most polluting stages are melting and refining; the level of COx emissions from electric arc furnaces depends on the carbon content of material input. The reduction of COx emissions to the steelmaking in the electric arc furnaces is possible by charge component selection and by the use of raw materials with reduced carbon content.